The Relationship between Psychosocial Factors and Affiliate Stigma in Parents of Children with ADHD: Systematic Literature Review - Aušraitė, Marija; Žardeckaitė-Matulaitienė, Kristina (Psichologija, 2022)
The aim of this study is to identify the psychosocial factors which are related with affiliate stigma in parents of children with ADHD through a systematic literature review. This review includes English publications from 2008 to 2022, which present the results of quantitative studies on the relationship between psychosocial factors and affiliate stigma in parents of children with ADHD. According to eligibility criteria, 7 articles were included in the review. The results showed that higher parental affiliate stigma is associated with lower parents’ psychosocial functioning (higher expressed depression, anxiety, lower self-esteem). It was also found that higher parental affiliate stigma is related to unfavorable behavior towards a child (higher expressed negativity/ less constructive parenting). The results also showed that higher parental affiliate stigma is associated with more expressed child’s difficulties (ADHD symptoms/ internalizing and externalizing difficulties).